LA EVALUACION DEL APRENDIZAJE Y SU INCIDENCIA EN EL LOGRO DE LOS OBJETIVOS DE LAS MATEMATICAS EN LOS CURSOS DE EDUCACION BASICA DEL COLEGIO NACIONAL ''CARACOL'' DE CARACOL EN EL PERIODO LECTIVO 2005-2006. - MIGDALIA DIAZ CHONG. (2008)
A EVALUATION OF LEARNING AND ITS IMPACT ON THE ACHIEVEMENT OF THE OBJECTIVES OF MATHEMATICS IN THE BASIC EDUCATION COURSES OF THE NATIONAL SCHOOL ''CARACOL'' OF CARACOL IN THE 2005-2006 SCHOOL PERIOD.